2012
DOI: 10.1016/j.devcel.2012.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Crb Apical Polarity Proteins Maintain Zebrafish Retinal Cone Mosaics via Intercellular Binding of Their Extracellular Domains

Abstract: Cone photoreceptors are assembled by unknown mechanisms into geometrically regular mosaics in many vertebrate species. The formation and maintenance of photoreceptor mosaics are speculated to require differential cell-cell adhesion. However, the molecular basis for this theory has yet to be identified. The retina and many other tissues express Crumbs (Crb) polarity proteins. The functions of the extracellular domains of Crb proteins remain to be understood. Here we report cell-type specific expression of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
153
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(167 citation statements)
references
References 54 publications
13
153
0
1
Order By: Relevance
“…It was reported to modify ligand-dependent Notch activity (Herranz et al, 2006;Richardson and Pichaud, 2010), and to mediate nonautonomous effects on cell survival (Hafezi et al, 2012). Other results suggested that the extracellular domain is engaged in homophilic interactions to stabilise Crb in the membrane, both in the Drosophila follicular epithelium (Fletcher et al, 2012) and in the zebrafish retina (Zou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported to modify ligand-dependent Notch activity (Herranz et al, 2006;Richardson and Pichaud, 2010), and to mediate nonautonomous effects on cell survival (Hafezi et al, 2012). Other results suggested that the extracellular domain is engaged in homophilic interactions to stabilise Crb in the membrane, both in the Drosophila follicular epithelium (Fletcher et al, 2012) and in the zebrafish retina (Zou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Based on indirect data some reports suggested the ability of Crb molecules to interact with other Crb molecules (Chen et al, 2010;Fletcher et al, 2012;Pellikka et al, 2002;Wei et al, 2006) or other proteins (Herranz et al, 2006;Richardson and Pichaud, 2010). Moreover, a recent study describes adhesion between zebrafish Crb molecules (Zou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A positive-feedback loop through homophilic interactions between extracellular domains of Crb in cis has been suggested to keep Crb on the apical membrane of follicle cells and thus ensures polarity (Fletcher et al, 2012). In addition, homophilic interactions in trans between the extracellular domains of Crb molecules on neighboring cells have been proposed to contribute to Crb stabilization on the apical membrane, both in Drosophila (Letizia et al, 2013;Röper, 2012) and in zebrafish (Zou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%